Designed Landscapes the Past, Present and Future - Salašová , Alena (4D Journal of Landscape Architecture and Garden Art, 2008)
The term “landscape” is usually used to define an element of the Earth’s surface. Given the fact that a landscape is continuous in time and space, its size and boundaries are defined using special purpose-built criteria. Primarily various natural processes and phenomena determine the development of landscape and its appearance. Approximately in the Laté Neolithic period in Central Europe, another significant phenomenon changing the landscape appeared among the complex of the natural factors - mán.
Keywords: Designed Landscape; Natural characteristics; Renaissance